Positive Psychology in Christian Perspective : foundations, concepts, and applications - Hackney, Charles H., 1974- (Downers Grove : IVP Academic, 2021)
"Positive psychology is about fostering strength and living well-about how to do a good job at being human. Charles Hackney connects this still-new movement to foundational concepts in philosophy and Christian theology. He then explores topics such as subjective states, cognitive processes, and the roles of personality, relationships, and environment"--
Includes bibliographical references (p. 269-328) and index.
Keywords: Christianity -- Psychology; Psychology and religion; Positive psychology